ASUPAN LEMAK JENUH DAN OBESITAS SENTRAL PADA IBU RUMAH TANGGA USIA 30-49 TAHUN (Jurnal Kesehatan Siliwangi, 2022)
Central obesity is excess fat concentrated in the abdomen. One of the risk factors for central obesity is smoking, lack of physical activity, and excess fat intake. This study aims to determine the description of saturated fat intake and central obesity in housewives aged 30-49 years in Sarimahi Village, Ciparay District in 2021. The study design used in this study was cross-sectional. The number of research samples was 95 housewives aged 30-49 years in Sarimahi Village which were obtained randomly. Collecting data by measuring waist circumference, interview method using the Semi-Quantitative FFQ questionnaire to see the average consumption of saturated fat intake per day. Waist circumference data were measured using a waist circumference meter. The data was processed using univariate and bivariate analysis with a chi-square test. The results showed that 62 people (65.3%) had central obesity, as many as 65 people (68.4%) had an excess saturated fat intake, 60 people (63.17%) samples had an excess saturated fat intake with central obesity nutritional status.